COMPARISON OF WARM WATER FOOT HYDROTHERAPY WITH AND WITHOUT EPSOM SALT ON LOWER EXTREMITY EDEMA AMONG THIRD-TRIMESTER PREGNANT WOMEN - Sartika; Sylvia Meristika Rachman; Noorlinda (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Lower extremity edema is a common discomfort experienced by third-trimester pregnant women due to physiological changes during pregnancy. This study aimed to analyze the effectiveness of foot hydrotherapy with Epsom salt in reducing lower extremity edema among third-trimester pregnant women in Weru District, Cirebon Regency. This study used a quasi-experimental pretest-posttest control group design involving 30 third-trimester pregnant women selected using purposive sampling. Respondents were divided into an intervention group receiving foot hydrotherapy with Epsom salt and a control group receiving warm water foot hydrotherapy only. Data were analyzed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test. The results showed significant reductions in edema scores in the Epsom salt group (p = 0.001) and warm water group (p = 0.008). The Mann-Whitney U Test also demonstrated a significant difference between groups (p = 0.001), indicating that foot hydrotherapy with Epsom salt was more effective than warm water hydrotherapy alone in reducing lower extremity edema. Foot hydrotherapy with Epsom salt may be recommended as a simple, safe, affordable, and non-pharmacological complementary intervention for reducing edema among third-trimester pregnant women.